Rule of wolves - Bardugo, Leigh (New York ; Imprint, 2021)
As Fjerda's massive army prepares to invade, Nikolai Lantsov will summon every bit of his ingenuity and charm to win this fight, and Zoya Nazyalensky must embrace her powers to become the weapon her country needs, meanwhile Nina Zenik risks discovery and death as she wages war on Fjerda from inside its capital.
A novel of the Grishaverse.
Keywords: Queens -- Juvenile fiction; Kings and rulers -- Juvenile fiction; Imaginary wars and battles -- Juvenile fiction; Generals -- Juvenile fiction; Demonology -- Juvenile fiction; Kings, queens, rulers. etc. -- Fiction; Fantasy fiction; Young adult fiction